2011
DOI: 10.1038/cmi.2010.66
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in patients with type 1 diabetes: a condition with distinct changes in intestinal immunity?

Abstract: Two common chronic childhood diseases-celiac disease (CD) and type 1 diabetes (T1D)-result from complex pathological mechanisms where genetic susceptibility, environmental exposure, alterations in intestinal permeability and immune responses play central roles. In this study, we investigated whether these characteristics were universal for CD independently of T1D association. For this purpose, we studied 36 children with normal small-bowel mucosa and 26 children with active CD, including 12 patients with T1D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
3
11
1
Order By: Relevance
“…Upregulated FoxP3 expression may counterbalance the loss of mucosal integrity by maintaining immune tolerance in the small intestine of patient with both celiac disease and T1D [137] . Contrary, a low expression of the tight junction protein 1 (TJP1) serving as a marker of intestinal mucosa integrity has been found in patients with both T1D and celiac disease [136,138] . Also gliadin and tTG IgA antibodies were the highest in these patients [138] .…”
Section: T-regulatory Associated Immunitymentioning
confidence: 98%
See 1 more Smart Citation
“…Upregulated FoxP3 expression may counterbalance the loss of mucosal integrity by maintaining immune tolerance in the small intestine of patient with both celiac disease and T1D [137] . Contrary, a low expression of the tight junction protein 1 (TJP1) serving as a marker of intestinal mucosa integrity has been found in patients with both T1D and celiac disease [136,138] . Also gliadin and tTG IgA antibodies were the highest in these patients [138] .…”
Section: T-regulatory Associated Immunitymentioning
confidence: 98%
“…Contrary, a low expression of the tight junction protein 1 (TJP1) serving as a marker of intestinal mucosa integrity has been found in patients with both T1D and celiac disease [136,138] . Also gliadin and tTG IgA antibodies were the highest in these patients [138] . These results may reveal that intestinal permeability is most severely impaired in patients with these two immunological diseases in combination [138] .…”
Section: T-regulatory Associated Immunitymentioning
confidence: 98%
“…Recently, in samples from the small bowel mucosa from patients with celiac disease and type 1 diabetes a low expression of tight junction protein 1 (TJP1) mRNA has been observed, indicating an increase in intestinal permeability that might represent a causative factor. Furthermore, the highest expression of Forkhead box P3 (FoxP3) mRNA, a marker of regulatory T cells was observed, suggesting an increased immunoregolatory mechanisms (Uibo et al, 2011). The mean prevalence of celiac disease in type 1 diabetes is about 8%, with an extremely variable range (from 1% up to 11%) (Kakleas et al, 2010), almost 10-20 fold higher than observed in general pediatric population (Maki et al, 2003).…”
Section: Celiac Disease and Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…An immature or damaged mucosa makes the mucous barrier more permeable, which can result in an allergic or autoimmune reaction in genetically predisposed individuals 9,10 . Uibo et al 11 detected the lowest expression of tight junction protein 1 (TJP1) mRNA in small bowel mucosa samples from celiac patients with diabetes mellitus type 1, indicating an increase in intestinal permeability. Furthermore, these samples displayed the highest expression of forkhead box P3 (FoxP3) mRNA, a marker of regulatory T cells, when compared with controls and celiac patients 11 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Uibo et al 11 detected the lowest expression of tight junction protein 1 (TJP1) mRNA in small bowel mucosa samples from celiac patients with diabetes mellitus type 1, indicating an increase in intestinal permeability. Furthermore, these samples displayed the highest expression of forkhead box P3 (FoxP3) mRNA, a marker of regulatory T cells, when compared with controls and celiac patients 11 . Antigen presenting cells (APC), which present antigens to T cells of the intestinal mucosa, are vital to the immunological processes.…”
Section: Pathophysiologymentioning
confidence: 99%